Political Reconstruction of Presidential Threshold Law Judging From the Presidential System and Simplification of Political Parties - Wardhana, Allan Fatchan Gani; Ghafur, Jamaludin (Law Research Review Quarterly, 2018)
The requirement of presidential threshold (PT) as regulated in article 222 Act No. 7 Year 2017 about General Election is no longer urgent to be applied in simultaneous general election. The requirement violates against the principles of justice general elections since it ellipse the rights of new political parties to propose candidates of president and vice president. On the other hand, viewing from the presidential system itself, PT requirement in the article 222 Act of General Election has an impairment and needs to reconstruct. This study emphasizes on two issues. First, the urgency to reconstruct political law of PT from the perspectives of presidential system and the simplification of political parties. Second, the concept of PT in the next simultaneous general election. This study results on, first, that in a presidential system, PT is considered as a requirement for the chosen and not a requirement for nominating president and vice president. In presidential systems, the presidential elections do not depend on the results of the legislative elections. Therefore, making the results of the legislative election as a condition for nominating the president and vice president is a violation of the presidential system. Second, PT provisions in terms of nomination requirements should no longer be needed because the purpose of implementing PT is to present a simplification party system and to garner majority support from the parliament against the elected president and vice president will be automatically implemented from the results of simultaneous general elections.